Gut microbiome composition changes in obstructive sleep apnoea syndrome also in relation to excessive daytime sleepiness - Mariana Fernandes; Orazio Palmieri; Stefano Castellana; Matteo Spanetta; Tiziana Latiano; Clementina Lupo; Claudia De Masi; Christian Cardile; Carmen Calvello; Francesca Izzi; Fabio Placidi; Tommaso Mazza; et al. (Brain Research Bulletin)
Introduction: Obstructive sleep apnoea syndrome (OSAS) is considered a risk factor for several comorbidities. Alteration in gut microbiome was documented in OSAS animal models and in paediatric patients. This study analysed gut microbiome composition in adult patients with OSAS compared to healthy controls. Further, the effect of excessive daytime sleepiness (EDS) on gut microbiome was evaluated. Methods: Adult patients with OSAS underwent polysomnographic recording and completed the Epworth Sleepiness Scale (ESS) to assess EDS. Faecal samples were collected and compared between patients and healthy controls. Composition, community diversity, differences in taxa abundance profiles and sample dysbiosis were evaluated through 16S metagenomics and multiple bioinformatics algorithms. OSAS patients were distributed in two groups according to EDS (ESS score≥10) to assess differences in clinical, polysomnographic and faecal data. Results: Twenty-three OSAS patients were compared to 44 healthy controls. Patients presented significant differences of gut microbiome biodiversity, specifically in qualitative alpha diversity metrics (Faith’s PD Kruskal-Wallis test, p-value=0.003; Number_of_Observed_Features, p-value =0.001). OSAS patients tend to cluster together, at least for Jaccard and Unweighted UniFrac distance-based PERMANOVA tests (q-values=0.02 and =0.003, respectively). Several taxa were detected as different in abundance between OSAS patients and healthy controls, although, globally, OSAS patients cannot be considered as “dysbiotic”. Differences in bacteria composition were evident between OSAS patients with and those without EDS. Conclusions: OSAS is associated with gut microbiome alteration in adult patients. EDS in OSAS seems to characterize a different gut microbiome composition, although it can be only hypothesized a gut-mediated effect on EDS in OSAS.